Kinetic adsorption of drugs using carbon nanofibers in simulated gastric and intestinal fluids - ÇALIŞKAN SALİHİ, ELİF (My University, 2022)
Two different classes of drugs were selected to test the adsorption capacity of carbon nanofibers as a greener new generation alternative adsorbent in simulated gastric and intestinal fluids. Kinetics of the promethazine and trimethoprim adsorption were analyzed using Lagergren first order and Pseudo second order models. Intraparticle diffusion graphs were also plotted to discuss the adsorption mechanism. Kinetic data showed the significance of boundary layer effect for both of the drugs and the presence of intraparticle diffusion as the other rate controlling step for the promethazine adsorption. Giles isotherms showed the high affinity of drug molecules to the adsorbent. Maximum adsorption capacity of drugs was calculated using Langmuir model as 18.35 and 41.15 mg/g for trimethoprim and 95.24 and 80.65 mg/g for promethazine in simulated gastric fluid (SGF) and simulated intestinal fluid (SIF), respectively. Trimethoprim adsorption was under favor of hydrophobic interaction and pi-pi dispersion interactions while promethazine adsorption was through cation exchange where the electrostatic attraction is an important force with the contribution of dispersion interactions.
Keywords: Kimya; Fizikokimya; Temel Bilimler; Chemistry; Physical Chemistry; Natural Sciences; KİMYA, FİZİKSEL; Temel Bilimler (SCI); CHEMISTRY, PHYSICAL; CHEMISTRY; Natural Sciences (SCI); Yüzeyler ve Arayüzler; Yüzeyler, Kaplamalar ve Filmler; Fiziksel ve Teorik Kimya; Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Surfaces and Interfaces; Surfaces, Coatings and Films; Physical and Theoretical Chemistry; Chemistry (miscellaneous); General Chemistry; Physical Sciences; adsorption; carbon nanofibers; kinetics; promethazine; trimethoprim; BIOCOMPATIBILITY; CLASSIFICATION; ENTEROSORBENTS; EQUILIBRIUM; ADSORBENTS; ISOTHERMS; CAPACITY; REMOVAL; AGENTS; WATER; adsorption; carbon nanofibers; kinetics; promethazine; trimethoprim